Optimization of Time in the Esterification Process of Jelantah Oil With Anova Analysis - Eka Megawati; Adittya Octavian Perdana Putra; Norhan Effendi; Yuniarti Yuniarti (EduChemia (Jurnal Kimia dan Pendidikan), 2021)
Used cooking oil is oil from frying which is an unused material. The processing of used cooking oil into biodiesel is expected to reduce household waste and become a new and renewable energy source. The first step in making biodiesel is the esterification process by measuring the value of free fatty acids. The purpose of this study was to determine the optimum time used during the esterification process and to compare the volume of using sulfuric acid (H2SO4) catalyst using the Anova method. The research was conducted using an experimental method. The variables used in this study were the deposition time of 12 hours to 25 hours and the volume of catalyst compared was 2 ml and 4 ml for every 200 ml of used cooking oil. Based on the results of the analysis, it was found that the optimum conditions that can be used in the deposition process are at 18 hours using 4 ml of catalyst. Based on the results of ANOVA analysis, it can be concluded that the calculated F value (0.002) <F table (94.196), it means that the FFA value of the 2 and 4 ml catalyst variations does not have a significant difference. faster process.